WOMEN UNDER THE SOVEREIGNITY OF MARRIAGE IN THE SHORT STORY â€œKETIKA PERKAWINAN HARUS DIMULAIâ€ BY OKA RUSMINI: FEMINIST - MARXIST CRITICISM - Pamardiningtyas, Sih Mangesthi (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2019)
This article discusses Oka Rusmini’s short story entitled Ketika Perkawinan Harus Dimulai, by utilizing the theory of Feminist - Marxist criticism to identify the portrayal of female characters related to Karl Marx’s class conflict and alienation. The discussion aimed to reveal that woman subordination is the result of social relations, and that men’s efforts to achieve their demands for control of women’s labor and sexual faculties have been delivered in the literary work. The analysis showed that the main character in the story struggled in her life in holding on to her commitment to prove that women can live for herself without being controlled by others. Therefore, Ketika Perkawinan Harus Dimulai is a critique towards patriarchal ideology and oppression towards women.